2021
DOI: 10.1002/cti2.1340
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of T‐cell repertoires with public COVID‐19‐associated T‐cell receptors in pre‐pandemic risk cohorts

Abstract: Objectives T cells have an essential role in the antiviral defence. Public T‐cell receptor (TCR) clonotypes are expanded in a substantial proportion of COVID‐19 patients. We set out to exploit their potential use as read‐out for COVID‐19 T‐cell immune responses. Methods We searched for COVID‐19‐associated T‐cell clones with public TCRs, as defined by identical complementarity‐determining region 3 (CDR3) beta chain amino acid sequence that can be reproducibly detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Given that the severity of COVID-19 increases with age (41) and that we have shown that depth and breadth of the T cell response measured by this assay increases with disease severity, it is possible that diagnostic sensitivity could be lower in younger individuals. However, an analysis of the representation of public SARS-CoV-2-specific TCRs has suggested that representation of these TCRs is higher among individuals < 60 years of age compared with those older than 60 years of age (42). Based on these divergent data, additional analyses are needed to assess the sensitivity of the assay in younger and asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the severity of COVID-19 increases with age (41) and that we have shown that depth and breadth of the T cell response measured by this assay increases with disease severity, it is possible that diagnostic sensitivity could be lower in younger individuals. However, an analysis of the representation of public SARS-CoV-2-specific TCRs has suggested that representation of these TCRs is higher among individuals < 60 years of age compared with those older than 60 years of age (42). Based on these divergent data, additional analyses are needed to assess the sensitivity of the assay in younger and asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Further insights are also provided by using sequence information based ML methods. In Simnica et al (168), COVID-19 public TCRs are investigated. GLIPH2 (81), one of the dissimilarity-based methods we reviewed, was used to cluster TCRs and select COVID-19 related TCRs by Student's T-test (similar to Emerson et al (16) introduced as one of the hypothesis test based methods).…”
Section: Repertoire Analysis For Covid-19mentioning
confidence: 99%
“…A number of publications have reported sequences of T cell receptors (TCRs) recognizing some immunodominant epitopes of SARS-CoV-2 (Shomuradova et al, 2020; Chaurasia et al, 2021; Minervina et al, 2021; Snyder et al, 2020). It was demonstrated that TCRs specific to some epitopes are public (Shomuradova et al, 2020; Simnica et al, 2021; Nguyen et al, 2021) and have a high degree of mutual similarity, which is sometimes accompanied by strong biases in variable (V) and joining (J) gene usage. According to the structural data, the latter can be explained by germline-based epitope recognition (Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%